Conjunto de bases gaussianas de qualidade dupla zeta para os átomos de Rb até Xe - Barros, Cezar Laurence (2010)
All-electron contracted Gaussian basis set of double zeta valence quality plus polarization functions (DZP) for the atoms from Rb to Xe is presented. This set was augmented by addition of diffuse functions (s, p, d, and f symmetries) that were optimized for the anion ground states and that are critical for an accurate description of electron affinity, polarizabilities, optical rotation, and hydrogen bonding. Besides, Douglas-Kroll-Hess (DKH) basis set for fourth-row elements is reported. We have recontracted the original DZP basis set, i.e., the values of the contraction coefficients were re-optimized using the relativistic DKH Hamiltonian. This extends earlier works on segmented contracted DZ basis set for atoms HKr. Our sets along with ab initio methods and density functional theory were used to calculate ionization energies of some atoms and spectroscopic constants and static electric properties of a sample of molecules and, then, comparison with results obtained with other basis sets and with experimental data reported in the literature was done. One verifies that our results give good agreement with experimental and benchmark values